Cultural discourses in Nigerian films: A multimodal study of Anikulapo and Elesin Oba (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
The immense growth of Nollywood or Nigerian film industry, in recent years, has made it a force to be reckoned with especially the expedient role it plays has a main participant in the African and global film market. Despite this growth, few attentions have been paid to the multimodal elements of these films, which is essential in understanding the meanings and messages conveyed. Therefore, this study takes a paradigm shift from existing scholarships by exploring the multimodal meanings embedded in film discourse. Drawing on Kress and van Leeuwen’s (2006) visual grammar framework, this study examines how Nigerian filmmakers employ different semiotic modalities to create meaning, convey messages, evoke thoughts and emotions, and tell stories through the application of the visual, linguistic, aural, and gestural elements within the selected films. Kunle Afolayan’s Anikulapo and Biyi Bandele’s Elesin Oba form the data base for this study. The findings from the study exposes the complex interplay of semiotic modes in the storytelling process, as well as, bringing to fore, the intricate and culturally significant aspects of Nollywood cinemas. The study concludes that an in-depth understanding of the narrative techniques employed by Nollywood films is pertinent in enriching African cinema discourses.
Keywords: multimodal discourse analysis, Nollywood films, visual grammar, Anikulapo, Elesin Oba; multimodal discourse analysis; Nollywood films; visual grammar; Anikulapo; Elesin oba